AI-Enhanced TPACK with a Modeling the Way Approach for Conceptual Development and Strengthening Representational Fluency in Islamic Education - Shidqi Ahyani; Laily Nur Arifa; Fahim Khasani; Sulistya Umie Ruhmana Sarie (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
Artificial Intelligence (AI) is increasingly reshaping pedagogical practices in higher education, yet its potential for conceptual restructuring in Islamic teacher education remains underexplored. This study develops and evaluates a model called Modeling the Way, based on AI-assisted TPACK learning, aimed at reducing conceptual misunderstandings and enhancing multi-representational skills among Islamic Religious Education students at UIN Maulana Malik Ibrahim Malang. Using a sequential exploratory mixed-methods design, qualitative findings from interviews and observations informed the development of AI-supported learning activities. A subsequent implementation demonstrated that AI-enabled modelling, guided practice, independent application, and reflective feedback facilitated cognitive conflict and strengthened representational fluency. Students shifted from relying on verbal recall to a flexible transformation of concepts across visual, symbolic, and contextual forms, while previously persistent misconceptions were reorganized into coherent conceptual structures. The findings suggest that when integrated intentionally, AI functions as a cognitive partner that amplifies pedagogical reasoning and conceptual development within the TPACK framework. This study offers theoretical insights and practical guidance for advancing technology-mediated learning innovations in Islamic teacher education. Broader application and longitudinal evaluation are recommended to examine long-term conceptual stability and ethical implications of AI in religious learning environments.